THE EFFECTIVENESS OF GALLERY WALK MODEL ON THE ACTIVITIES AND SKILLS OF WRITING PANTUN AT GRADE V SD NEGERI 59 GAROTIN, KECAMATAN ANGGERAJA, KABUPATEN ENREKANG - Iyyut Hajrianti Mandrasari; Andi Sukri Syamsuri, Syafruddin (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This study aimed to determine the effectiveness of implementing the Gallery Walk model on the learning activities and pantun writing skills of the fifth-grade students at SD Negeri 59 Garotin, Kecamatan Anggeraja, Kabupaten Enrekang. The type of experimental research used in this study was Quasi-Experimental Research with a Non-Equivalent Control Group Design. The students’ learning outcomes were analyzed using a t-test after carrying out the prerequisite tests, namely the normality test and the homogeneity test. The results showed that the average percentage of students' learning activities in the experimental class was 91.06%, which was categorized as very high, while the average percentage in the control class was 76.78%. The results also showed that the average value of students’ learning outcomes in the experimental class was 87.36%, while the average value in the control class was 77.05%. In addition, the result of the t-test revealed that the value of tcount (2.875) > ttable (2.032) with Sig (2-tailed) < 0.05, namely 0.007. Thus, the hypothesis was proven to be accepted.